Does the Use of Social Media Tools in Classrooms Increase Student Commitment to Corporate Social Responsibility? - Rodríguez-Gómez, Sara; Garde-Sánchez, Raquel; Arco-Castro, María Lourdes; López-Pérez, María Victoria (Frontiers in Psychology, 2020)
The increase in the demand for companies to make ethical decisions has necessitated the introduction of corporate social responsibility (CSR) in the training of business students. To adequately focus CSR instruction, it is appropriate to know the students’ perceptions of the ethical and social responsibility requirements that companies must assume, as well as their commitment to the various stakeholders and the reasons that lead them to choose whether to act ethically. At the same time, teaching methods are changing towards new forms that facilitate more autonomous learning by students. Web 2.0-based methods and social-media tools have proven useful for this purpose, especially when training students in issues of ethics and CSR, as their emotions and values come into play, and these tools have proven effective in transmitting and integrating these concepts. The aim of this work is both to examine students’ perceptions of ethical and CSR practices, their commitment to different stakeholders and the reasons that lead them to act in a socially responsible way and, on the other hand, to see how this perception can be improved when social-media tools are used in classrooms to teach these ideas. To this end, a survey was carried out with first-year students at two points in time: at the beginning of the semester and at the end of it, once the training activities on CSR and ethics planned using Web 2.0 and social-media tools had been conducted.